Accuracy of the small field dosimetry using the monte carlo and sequential dose calculation algorithms of Multiplan treatment planning system within and beyond heterogeneous media for Cyberknife M6 unit. (September 2016) - Serin, E.; Codel, G.; Cebe, M.S.; Mabhouti, H.; Pacaci, P.; Sanli, E.; Doyuran, M.; Kucukmorkoc, E.; Altinok, A.; Canoglu, D.; Kucuk, N.; Acar, H.; et al.
Abstract : Purpose: In this study, dosimetric accuracy of Monte Carlo (MC) advanced dose calculation and sequential algorithms of Multiplan treatment planning system were investigated for small radiation fields incident on homogeneous and heterogeneous geometries. Methods: Small open fields of fixed cones of Cyberknife M6 unit 10 × 10 to 50 × 50 mm 2 were used for this study. The fields were incident on phantom containing lung, air and bone inhomogeneities and also homogeneous phantom. Using the same film batch, the net OD to dose calibration curve was obtained using CK with the 60 mm fixed cone by delivering 0–800 cGy. Films were scanned 48 h after irradiation using an Epson 1000XL flatbed scanner. The dosimetric accuracy of MC and sequential algorithms in the presence of the inhomogeneities was compared against EBT3 film dosimetry Results: Open field tests in a homogeneous phantom showed good agreement between two algorithms and film measurement For MC algorithm, the minimum gamma analysis passing rates between measured and calculated dose distributions were 99.7% and 98.3% for homogeneous and inhomogeneous fields in the case of lung and bone respectively. For sequential algorithm, the minimum gamma analysis passing rates were 98.9% and 92.5% for homogeneous and inhomogeneous fields respectively for used all cone sizes. In the case of the air heterogeneity, the differences were larger for both calculation algorithms. Overall, when compared to measurement, the MC had better agreement than sequential algorithm. Conclusions: The MC calculation algorithm in the Multiplan TPS is an improvement over the existing sequential algorithm. Dose discrepancies were observed for in the presence of air inhomogeneities.